REALIZATION OF NITROGEN FIXATION POTENTIAL OF TN5-MUTANTS Bradyrhizobium japonicum IN SYMBIOSIS WITH SOYBEAN PLANTS - N. A. Vorobey; S. Ya. Kots; P. M. Mamenko (Biotechnologia Acta, 2013)
Nodule bacteria of different rate and dynamics of nitrogenase activity in symbiosis with soybean plants were selected as the result of investigation of Bradyrhizobium japonicum Tn5-mutants. Insertion nature of mutations that lead to appearance of KmR forms of B. japonicum with changed symbiotic properties was proved by PCR- technique. Tn5-mutants of B. Japonicum were analyzed for their symbiotic characteristics in vegetative and small plot experiments during different ontogenesis stages of various soybean plants (Annushka, Vasylkivska, Maryana, Colbi) that cover three cultivar maturity groups. It was established that dynamics and intensity of nitrogen assimilation in soybean root nodules depended on microsymbiont genotype, as well as cultivar and development stage of host plant. It was shown that Tn5-mutants obtained with the plasmid pSUP5011::Tn5mob were more efficient in symbiosis with early-maturing soybean cultivars Annushka and Vasylkivska, while mutants obtained with the pSUP2021::Tn5 plasmid — more efficient in symbiosis with Maryana and Colbi soybean cultivars with the prolonged vegetation period. Tn5-mutants of B. japonicum Т66, Т21-2, В-18 and В-20 with advanced complementarity properties, that ensure higher nitrogen fixation rates in soybean plants during budding and budding–early flowering stages resulting in yield increase as comparing to the B. Japonicum strains 646 and 634b were selected. The possibilities of creation of polycomponent inoculum for soybean cultivars belonging to different maturity groups based on the rhizobia strains with various intensity and dynamics of nitrogen fixation activity are discussed.